Answer:
Idont know
Step-by-step explanation:
Since both are equivalent to y, the equations must be equivalent.
x^2-x-3= -3x+5
x^2+2x-8=0
(x+4)(x-2)=0
x=-4, x=2
Plug the values of x in to either equation
y=-3(-4)+5
y= 12+5
y=17
y= -3(2)+5
y=-6+5
y=-1
Final answer: (-4,17) and (2,-1)
I thin the best answer among the following choices base on the data you have given and the formulas, to be honest I didn't really understand the instructions but in your diagram, this is just my suggestion but no an answer, the value of #1 2nd option from the left of the first line and the #2 is the last choice from the first line. I hope this would help